Efektivitas Infra Red Yang Dipadukan Dengan Exercise Terhadap Penyakit Low Back Pain - Muhammad Hafidz Al Fathan; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Low back pain (LBP) is one of the most common musculoskeletal problems and can lead to limited activity and reduced quality of life. This condition is often experienced by individuals whose jobs involve sitting for long periods, poor ergonomic work postures, or excessive physical activity. One non-invasive physical therapy method commonly used to reduce LBP pain is Infra Red (IR). IR works by producing superficial heat that can improve blood flow, reduce muscle spasms, and lower pain sensitivity. In addition, providing exercise or therapeutic workouts aims to increase flexibility, muscle strength, and lumbar stability. Combining Infra Red with exercise is expected to provide more effective results in managing LBP. This study is a literature review conducted using the PICO approach to search databases such as PubMed, ScienceDirect, and Google Scholar. The articles used are Randomized Controlled Trials (RCTs) published in the last five years. The review results show that applying Infra Red combined with exercise significantly reduces pain intensity, improves flexibility of the lower back muscles, increases range of motion (ROM), and enhances functional ability in patients with LBP. Applying Infra Red for 15–20 minutes combined with regular exercise for 4–6 weeks provides optimal results for patients with non-specific LBP. Based on these findings, it can be concluded that combining Infra Red and exercise is effective in reducing pain and improving function in patients with Low Back Pain.